2020
DOI: 10.1007/s00417-020-04939-7
|View full text |Cite
|
Sign up to set email alerts
|

Tendon elongation with bovine pericardium in strabismus surgery—indications beyond Graves’ orbitopathy

Abstract: Background For some patients with complex ocular motility disorders, conventional strabismus surgery is insufficient. Surgery with tendon elongation allows correction of larger angles and maintains a sufficient arc of contact for rectus muscles. This study reports results for tendon elongation with bovine pericardium (Tutopatch®) in indications other than Graves’ orbitopathy in which it is already widely used. Methods We reviewed the records of all patients who underwent surgery with Tutopatch® in our instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Other groups have also reported satisfactory results ( 140 , 141 ). To reduce IR muscle restriction, tendon elongation uses homologous scleral grafts, polytetrafluoroethylene (Goretex), silicone, bovine pericardium, ( 142 ), or fascia lata ( 143 ). Jefferis et al ( 127 ) reported favorable outcomes after prioritizing downgaze alignment (rather than primary gaze alignment) to avoid downgaze diplopia.…”
Section: Squint Surgerymentioning
confidence: 99%
“…Other groups have also reported satisfactory results ( 140 , 141 ). To reduce IR muscle restriction, tendon elongation uses homologous scleral grafts, polytetrafluoroethylene (Goretex), silicone, bovine pericardium, ( 142 ), or fascia lata ( 143 ). Jefferis et al ( 127 ) reported favorable outcomes after prioritizing downgaze alignment (rather than primary gaze alignment) to avoid downgaze diplopia.…”
Section: Squint Surgerymentioning
confidence: 99%
“…Therefore, conventional strabismus surgery is commonly insufficient in cases with a large-angle deviation. To maximize the weakening effects, Hedergott et al suggested tendon elongation techniques using bovine pericardium [ 77 ].…”
Section: Managementmentioning
confidence: 99%
“…In brief, pericardium grafts have been applied to correct intracardiac and diaphragm defects (Ricci et al, 2014;Yaliniz et al, 2014;Ascaso et al, 2021), as well as ischemic ventricular septal defect after acute MI (Mihalj et al, 2022). On the other hand, non-cardiac pericardium-based applications include replacement of brain dura mater (Sun et al, 2018), bleb repair, conjunctival reconstruction, cover of severe corneal wound or tendon elongation in the eye (Niegowski et al, 2020;Ashena et al, 2021;Hedergott et al, 2021;Chen et al, 2022), odontology (Solakoğlu et al, 2022) and eardrum reconstruction (de Dorldodot et al, 2013;Sainsbury et al, 2022). Furthermore it has been employed to generate a variety of bioprostheses such as vascular grafts, patches for abdominal or vaginal wall reconstruction and heart valves (Rémi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%